Analisis Dampak Pembangunan Kampus Ii Iain Batusangkar Terhadap Ekonomi Masyarakat Di Nagari Cubadak - Vicy Andriany; Fredi Fransisko (Saqifah: Jurnal Hukum Ekonomi Syariah, 2021)
The problem in this research is the construction of the IAIN Batusangkar II campus which is feared to reduce productive land so that it has an impact on people's livelihoods. The purpose of this study was to determine the impact of the construction of Campus II IAIN Batusangkar on the economy of the community in Nagari Cubadak. The type of research used is field research with a qualitative descriptive approach. The data sources in this study were the Wali Nagari Cubadak and entrepreneurs in Nagari Cubadak. The results of the study found that there were new livelihoods for the community which in the end were expected to become additional income so that economic conditions could improve. The construction of Campus II IAIN Batusangkar has a positive impact on the surrounding community, with new business opportunities for the community around Campus II of IAIN Batusangkar. The local government needs to regulate development policies in Nagari Cubadak so that there is no chaos due to the uncontrolled pace of development and to protect productive agricultural lands in Nagari Cubadak so as not to be eroded by the pace of development.